PENGARUH FAKTOR BUDAYA, MOTIVASI, REGULASI, DAN PEMAHAMAN TENTANG ZAKAT TERHADAP KEPUTUSAN MUZAKKI UNTUK MEMBAYAR ZAKAT MAAL (Studi Para Muzakki di Kota Sabang) - Rina Rizkia; Muhammad Arfan; M. Shabri (Program Magister Akuntansi Unsyiah, 2014)
This study is aimed to examine the factors that influence the decision Muzakki to pay zakat maal. Factors affecting the cultural, motivation, regulation, and understanding of the zakah. Respondents were sampled in this study is the Muzakki who live in the city of Sabang. Total Respondents many as 150 people. The sample selection is done by using Slovin formula with convenience sampling method. Methods of data analysis are binary logit logistic regression. The results of this study showed that simultaneous culture, motivation, regulation, and an understanding of the zakah affect the decision Muzakki to pay his zakah Maal. Partially, as whole independent variable, namely culture, motivation, regulation, and an understanding of zakah positive and significant effect on the decision for Muzakki to pay zakah maal. Keywords: culture, motivation, regulations, understanding of the zakah, and the decision Muzakki to pay zakah maal.